Mengatasi Tantangan Pelayanan Publik: Analisis Inovasi Mal Pelayanan Publik Kota Magelang - Afifah, Afifah; Orbawati, Eny Boedi; Mahendradi, Mahendradi; Nugraha, Joko Tri (Jurnal Ilmiah Global Education, 2024)
Public Service is an activity or series of activities in order to meet service needs in accordance with laws and regulations. The purpose of the study is to analyze the innovation of Magelang City Public Service Mall and analyze the obstacles and solutions provided to overcome this The method used is a qualitative method with a case study approach. Data collection uses observations, interviews, and supporting documents. The data analysis techniques used are data condensation, data presentation, and conclusions. The results show that the innovation of Magelang City Public Service Mall has received a positive response from the community. New ideas from the government so that the creation of this Public Service Mall has been very helpful. Improvement efforts continue to be pursued to improve and improve the delivery of existing services in the Magelang City Public Service Mall. Innovation attributes that contain relative advantages, suitability, complexity, possibility, and convenience also show good results. However, for complexity, there are still several obstacles such as system problems, limited service time so it is necessary to make improvements.